Puffer fish poisoning: a case report - Islam Khan, Mohammad Monirul; Habib, Rahat Bin; Islam, Mohammad Didarul; Newaz , Md Shah (Community Based Medical Journal, 2019)
Puffer fish poisoning after consumption of this fish is one of the most common causes of poisoning among people in the coastal regions of Asia. Puffer fish poison (tetradotoxin) is one of the most toxic substances still found on earth; it is about 275 times more lethal poison than cyanide and fifty times more potent than strychnine or curare poison. Still no anti toxin or antidote is being discovered yet. On 6th January 2021, among five members of a single family, all of them ingested puffer fish after cooking, everyone developed toxic manifestations. Father died after three hours on the way to hospital, mother died after 17 hours during treatment and three daughters improved without any residual complication after getting supportive treatment in this hospital. CBMJ 2019 January: vol. 08 no. 01 P: 35-38